(untitled) (Docentes 2.0 Journal, 2023)
The constant change in the teaching and learning process and the demand for incorporating new educational methodologies are increasing at all educational levels. One widely accepted methodology is gamification, which emerged to incorporate game elements and provide an innovative learning environment. The present work was carried out under the inductive method, humanistic paradigm, with a qualitative approach, interpretative type, and narrative design of the topic. Its purpose was to analyze the influence of gamification on higher education students. The inquiry was divided into three sections: the first on student-focused motivation, the second on the main strategies used by teachers, and the last on the challenges of implementing this methodology at the university. The strategies that have influenced the student’s motivation were identified as the main result. The second term presents how teachers select the strategies for implementing gamification. Finally, the challenges, reflections, and suggestions for improving teaching practice using gamification are shared.